2018
DOI: 10.1186/s12935-018-0704-y
|View full text |Cite
|
Sign up to set email alerts
|

Silencing TRIP13 inhibits cell growth and metastasis of hepatocellular carcinoma by activating of TGF-β1/smad3

Abstract: BackgroundTRIP13 is highly expressed in several cancers and is closely connected with cancer progression. However, its roles on the growth and metastasis of hepatocellular carcinoma (HCC), and the underlying mechanism are still unclear.MethodsCombining bioinformatics with previous studies, the correlation between TRIP13 and HCC was predicted. TRIP13 expressions from 52 HCC patients and several cell lines were determined. The effects of silencing TRIP13 on cell viability, apoptosis, migration and invasion were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 51 publications
(39 reference statements)
3
41
1
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001 ACTN4 expression in HCC cells. Additionally, different with our result, an earlier research reported that TRIP13 facilitates HCC cell growth and metastasis through activating of TGF-β1/smad3 signaling [28].…”
Section: Discussioncontrasting
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001 ACTN4 expression in HCC cells. Additionally, different with our result, an earlier research reported that TRIP13 facilitates HCC cell growth and metastasis through activating of TGF-β1/smad3 signaling [28].…”
Section: Discussioncontrasting
confidence: 99%
“…Silencing TRIP13 could act as a tumor suppressor for liver cancer, which inhibited cell growth and metastasis in vivo and in vitro experiments (18). Overexpression of TRIP13 abrogated mitotic spindle checkpoint and induced proteasome-mediated degradation of MAD2 in multiple myeloma mainly through the Akt pathway.…”
Section: Discussionmentioning
confidence: 96%
“…The overexpression of KIF2C has been significantly associated with poor prognosis of HCC (Chen et al, 2017). TRIP13 is overexpressed in HCC tissues and can induce progression and invasion of HCC (Yao et al, 2018; FIGURE 11 | Kaplan-Meier survival and receiver operating characteristic (ROC) curves in training and validation datasets. Kaplan-Meier survival curves of overall survival for hepatocellular varcinoma (HCC) patients in the International Cancer Genome Consortium (ICGC) (A) and The Cancer Genome Atlas (TCGA) (B) set.…”
Section: Discussionmentioning
confidence: 99%